2010
DOI: 10.1002/app.33403
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of hybrid rice straw/sea weed polypropylene composites

Abstract: Rice straw (Rs)/polypropylene (PP) composites were prepared in the different ratio of 5 : 95, 10 : 90, 15 : 85, 20 : 80, 25 : 75, and 30 : 70 (Rs wt % : PP wt %) by an injection molding process. This work investigated the tensile strength (TS), bending strength (BS), and impact strength (IS) of the composites. From the results, it is observed that Rs20 : PP80 mixture composite showed better performance with mechanical properties (TS ¼ 26.2 MPa, BS ¼ 58 N/mm 2 , and IS ¼ 1.7 KJ/mm 2 ) among the composites pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The low value at high filler content may be due to the presence of so many filler ends in the composites, which could cause crack initiation and hence potential composite failure [22] . Concerning the above results, it is noted that the composites RS30 prepared by formulation as 30% RS in 70% PP exhibit better mechanical behaviour, which is an identical result of our earlier work [10] and henceforward, for this formulation, it would have to be supposed the optimised system for further experimental study.…”
Section: Results and Discussion Optimization Of Rs Content In Pp Composupporting
confidence: 74%
See 1 more Smart Citation
“…The low value at high filler content may be due to the presence of so many filler ends in the composites, which could cause crack initiation and hence potential composite failure [22] . Concerning the above results, it is noted that the composites RS30 prepared by formulation as 30% RS in 70% PP exhibit better mechanical behaviour, which is an identical result of our earlier work [10] and henceforward, for this formulation, it would have to be supposed the optimised system for further experimental study.…”
Section: Results and Discussion Optimization Of Rs Content In Pp Composupporting
confidence: 74%
“…In the last decade, bio-composite materials based on biodegradable polymer matrices and natural fibers as reinforcements have received significant scientific attention [6][7][8][9] . The fibers used to reinforce thermoplastics mainly include wood, cotton, flax, hemp, jute sisal, and sugarcane fibers [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Straw based materials are generally used as filler in thermoplastic polymers and used in the manufacture of particleboard and fiberboard with thermoset resins . Pristine and surface treated RS were used as additive in several thermoplastic polymers including polyethylene , polypropylene , polyvinylchloride , poly (lactic acid) , polystyrene , poly (caprolactone) , and poly (butylene succinate) .…”
Section: Introductionmentioning
confidence: 99%
“…At intermediate level of TD loading (40%), the population of the fibers is just right for maximum orientation and the fibers actively participate in stress transfer. High levels of TD content showed that the increased population of fibers leads to agglomeration and stress transfer gets blocked and the resulting composite property is again found to decrease 16, 17. Figures 3 and 4 show that with the increase of the TD content to the polymer composites, the Eb decreases and the TM increases.…”
Section: Resultsmentioning
confidence: 96%